ASUHAN KEBIDANAN KOMPREHENIF PADA NY.P DI WILAYAH KERJA PUSKESMAS KUIN RAYA BANJARMASIN - Maulida Rizki; Nur Cahyani Ari Lestari (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2022)
Comparing data from the Kuin Raya Health Center in 2019 to 2020. , the number of pregnant women in the Kuin Raya Health Center's working area decreased from 843 to 379 pregnant women. The declining achievements from 2019 to 2020 occurred in indicators of complete postpartum visits (KF 4), complete neonatal visits (KN), detection of maternal risk factors by the community, detection of risk factors by health workers, maternal complications handled, and referral of rest cases. maternal.Types of Research The type of research used in the preparation of the final project report is descriptive research with case study methods.From the results, the authors can draw the following conclusions: Subjective and objective data on care for pregnancy, childbirth, newborns, postpartum and family planning for Mrs. P have been collected and has been interpreted. Also can be drawn assessment/diagnose in all care is physiological. Data analysis does not require immediate action needs for collaboration and referrals to care for pregnancy, childbirth, newborns, postpartum and family planning for Mrs. Management has been arranged in accordance with the care provided for both pregnancy, childbirth, newborn, postpartum and family planning care in Mrs. P. Management has been carried out efficiently and safely in the care of pregnancy, childbirth, newborns, postpartum and family planning to Mrs. P. After being given comprehensive care, it can be concluded that Mrs. P underwent pregnancy, childbirth, newborns , postpartum and family planning without any complications (physiological). And the care that has been given is in accordance with the theory.